Evaluating risk for alcohol use disorder: Polygenic risk scores and family history. (10th March 2022) - Lai, Dongbing; Johnson, Emma C.; Colbert, Sarah; Pandey, Gayathri; Chan, Grace; Bauer, Lance; Francis, Meredith W.; Hesselbrock, Victor; Kamarajan, Chella; Kramer, John; Kuang, Weipeng; Kuo, Sally; et al.
Abstract: Background: Early identification of individuals at high risk for alcohol use disorder (AUD) coupled with prompt interventions could reduce the incidence of AUD. In this study, we investigated whether Polygenic Risk Scores (PRS) can be used to evaluate the risk for AUD and AUD severity (as measured by the number of DSM‐5 AUD diagnostic criteria met) and compared their performance with a measure of family history of AUD. Methods: We studied individuals of European ancestry from the Collaborative Study on the Genetics of Alcoholism (COGA). DSM‐5 diagnostic criteria were available for 7203 individuals, of whom 3451 met criteria for DSM‐IV alcohol dependence or DSM‐5 AUD and 1616 were alcohol‐exposed controls aged ≥21 years with no history of AUD or drug dependence. Further, 4842 individuals had a positive first‐degree family history of AUD (FH+), 2722 had an unknown family history (FH?), and 336 had a negative family history (FH−). PRS were derived from a meta‐analysis of a genome‐wide association study of AUD from the Million Veteran Program and scores from the problem subscale of the Alcohol Use Disorders Identification Test in the UK Biobank. We used mixed models to test the association between PRS and risk for AUD and AUD severity. Results: AUD cases had higher PRS than controls with PRS increasing as the number of DSM‐5 diagnostic criteria increased ( p ‐values ≤ 1.85E −05 ) in the full COGA sample, the FH+ subsample, and the FH? subsample. Individuals in the top decile of PRS had odds ratios (OR) for developing AUD of 1.96 (95% CI: 1.54 to 2.51, p ‐value = 7.57E −08 ) and 1.86 (95% CI: 1.35 to 2.56, p ‐value = 1.32E −04 ) in the full sample and the FH+ subsample, respectively. These values are comparable to previously reported ORs for a first‐degree family history (1.91 to 2.38) estimated from national surveys. PRS were also significantly associated with the DSM‐5 AUD diagnostic criterion count in the full sample, the FH+ subsample, and the FH? subsample ( p ‐values ≤6.7E −11 ). PRS remained significantly associated with AUD and AUD severity after accounting for a family history of AUD ( p ‐values ≤6.8E −10 ). Conclusions: Both PRS and family history were associated with AUD and AUD severity, indicating that these risk measures assess distinct aspects of liability to AUD traits. Abstract : We calculated polygenic risk scores (PRS) using variants having the same directions of effects in discovery datasets to exclude study‐specific findings and findings due to random variations. The PRS were significantly associated with AUD and AUD severity. Those in the top decile of PRS had odds ratios of 1.96 to develop AUD, comparable to odds ratios of the family history of AUD. PRS were also independent of family history and especially useful when family history information is not available.